Examination of dental implants removal - Dóra Iványi; Péter Kivovics (Hungarian Dental Association, 2018)
The aim of this research is to make a comparative interpretation of implant removals in the last four years in the Department of Community Dentistry. The applied data were obtained by x-rays, medical charts and patient management program, called FOGÁSZ, found in the Department of Community Dentistry. Data were evaluated with Microsoft Excel software. The last four years, 30 patients' 58 implants were removed in the Department of Community Dentistry. The average age was 64,3 (±8,8) years and 96,7% of the patients were aged 50 or over. 53,7% of the concerned individuals' inserted implants were removed. 20,0% of the patients lost their implants within six months from surgery. The removed implants were possessed 5,8 (±4,3) for years on average. 36,7% of the patients had fixed prosthesis supported implant and teeth, this was the most common prosthesis type. The prevalence of peri-implantitis around removed implants was 77,6%. Out of the partly edentulous patients, horizontal bone resorption was discernible in 50,0%. 12,1% of the removals were recommended because of inflammation before osseointegration. It is recommended not to plan any prostheses anchored at the same time to tooth and implant. Fixed prostheses simultaneously anchored on both tooth and implant may cause implant loss, because biomechanical aspects of anchoring behave differently in the bone. Prevention of peri-implantitis is a key factor in the success of implants, which can be achieved by proper oral hygiene. Periodontitis could also promote the development of peri-implantitis. Patients with periodontitis should be cured of inflammation before implantation. Important factor for osseointegration is the inflammation-free healing.